Frailty as determined by a comprehensive geriatric assessment‐derived deficit‐accumulation index in older patients with cancer who receive chemotherapy. Issue 24 (16th August 2016) - Cohen, Harvey Jay; Smith, David; Sun, Can‐Lan; Tew, William; Mohile, Supriya G.; Owusu, Cynthia; Klepin, Heidi D.; Gross, Cary P.; Lichtman, Stuart M.; Gajra, Ajeet; Filo, Julie; Katheria, Vani; et al.
Abstract : BACKGROUND: Frailty has been suggested as a construct for oncologists to consider in treating older cancer patients. Therefore, the authors assessed the potential of creating a deficit‐accumulation frailty index (DAFI) from a largely self‐administered comprehensive geriatric assessment (CGA). METHODS: Five hundred patients aged ≥65 years underwent a CGA before receiving chemotherapy. A DAFI was constructed, resulting in a 51‐item scale, and cutoff values were examined for patients in the robust/nonfrail (cutoff value, 0.0 < 0.2), prefrail (cutoff value, 0.2 < 0.35), and frail (cutoff value,  ≥ 0.35) groups. RESULTS: Two hundred and fifty patients (50%) were nonfrail, 197 (39%) were prefrail, and 52 (11%) were frail. Older patients (aged ≥ 80 years) and those who had lower education, were living alone, and had higher stage disease were associated with prefrail/frail status. Prefrail/frail patients were more likely to have grade ≥3 toxicity but not to have a dose delay or reduction, and they were more likely to discontinue drug and be hospitalized. The association with grade ≥3 toxicity was attenuated by controlling for a toxicity risk calculator, but the other outcomes were not. CONCLUSIONS: A deficit‐accumulation frailty index can be constructed from a CGA in older patients with cancer and can indicate the frailty status of the population. The frailty status so determined is associated both with outcomes likely because of chemotherapy toxicity and with those likely because of age‐related physiologic and functional deficits and thus can be useful in the overall assessment of the patient. Cancer 2016;122:3865–3872. © 2016 American Cancer Society. Abstract : It is feasible to derive a deficit‐accumulation frailty index as a summary measure of vulnerability from information collected in a comprehensive geriatric assessment for older patients with cancer. Frailty status so derived is associated with treatment outcomes, uncloudy toxicity, drug discontinuation, and hospitalizations.